2022
DOI: 10.3389/fendo.2021.750261
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte-Specific Inhibition of Mir221/222 Ameliorates Diet-Induced Obesity Through Targeting Ddit4

Abstract: MicroRNAs expressed in adipocytes are involved in transcriptional regulation of target mRNAs in obesity, but miRNAs critically involved in this process is not well characterized. Here, we identified upregulation of miR-221-3p and miR-222-3p in the white adipose tissues in C57BL/6 mice fed with high fat-high sucrose (HFHS) chow by RNA sequencing. Mir221 and Mir222 are paralogous genes and share the common seed sequence and Mir221/222AdipoKO mice fed with HFHS chow demonstrated resistance to the development of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…A similar effect associated with upregulation of miR-221-3p and miR-222-3p was observed in the white adipose tissue of C57BL/6 mice fed with high high-fat sucrose chow [ 66 ]. These observations indicated that miR-222 could promote the proliferation of preadipocytes and the accumulation of lipids in mature adipocytes by inhibiting lipolysis [ 67 ] and, therefore, the overexpression of miR-222 is linked to enhanced adipogenesis.…”
Section: Micrornas (Mirnas) In Breast Cancermentioning
confidence: 61%
“…A similar effect associated with upregulation of miR-221-3p and miR-222-3p was observed in the white adipose tissue of C57BL/6 mice fed with high high-fat sucrose chow [ 66 ]. These observations indicated that miR-222 could promote the proliferation of preadipocytes and the accumulation of lipids in mature adipocytes by inhibiting lipolysis [ 67 ] and, therefore, the overexpression of miR-222 is linked to enhanced adipogenesis.…”
Section: Micrornas (Mirnas) In Breast Cancermentioning
confidence: 61%
“…The role of miR-222-3p in GDM is unknown, but previous mechanistic studies implicate circulating miR-222-3p levels in both obesity and T2D ( 62 65 ). MiR-222-3p targets at least three experimentally validated genes of which low levels have been associated with T2D pathology: O-6-Methylguanine-DNA Methyltransferase ( MGMT ), Serine/threonine-protein phosphatase 2A 55 kDa regulatory subunit B-α isoform ( PPP2R2A ), and Reversion Inducing Cysteine Rich Protein With Kazal Motifs ( RECK ) ( 62 , 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…In mouse models of obesity, overexpression of miR-222-3p was associated with increased adiposity by targeting DNA damage inducible transcript 4 ( Ddit4 ) in adipocyte specific miR-221/222 knockout, which was associated with the suppression of the tuberous sclerosis complex 2 (TSC2)/mTOR complex 1 (mTORC1)/ribosomal protein S6 kinase (S6K) pathway ( 65 ). Circulating levels of miR-222-3p have been downregulated post-bariatric surgery induced weight loss in at least two studies ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…Signaling pathways include cytokine signaling in immune system [48], extracellular matrix organization [49], diseases of metabolism [50], hemostasis [51], innate immune system [52], metabolism of lipids [53] and metabolism [54] were linked with progression of PCOS. Altered expression of PLA2G5 [55], CASP1 [56], EDNRA (endothelin receptor type A) [57], F2RL1 [58], FOXP3 [59], DRD4 [60], COL6A3 [61], TIMP4 [62], SOCS1 [63], CD74 [64], TGFB1 [65], ATF5 [66], IRF7 [67], IRX3 [68], FOXC2 [69], STX1A [70], IL1RL1 [71], HHIP (hedgehog interacting protein) [72], ELOVL2 [73], BGN (biglycan) [74], POMC (proopiomelanocortin) [75], DOK5 [76], COL1A1 [77], POSTN (periostin) [78], SOD3 [79], ZNF423 [80], FABP5 [81], DDIT4 [82], KCTD15 [83], COL1A2 [84], MGAT2 [85], ENDOG (endonuclease G) [86], HSPA5 [87], CES1 [88], CYP19A1 [89], PLAC8 [90], CD36 [91], GIPR (gastric inhibitory polypeptide receptor) [92], ARG1 [93], MSR1 [94], DOCK2 [95], S1PR1 [96], OXTR (oxytocin receptor) [97], F11R [98], LEPR (leptin receptor) [99], AR (androgen receptor) [100], DKK3 [101], FOXO1 [102], PIK3CB [103], WWP1 [104], PHIP (pleckstrin homology domain interacting protein) [105], MPZL3 [106], FBXO2 [107], GUCY2C [108], ADRA2A [109], CHRNA5 [110], GLP2R [111], SDC3 [112], NFAT5 [113], PON2 [114], PRNP (prion protein) [115], DGKE (diacylglycerol kinase epsilon) [116], ARHGAP21 [117], COQ2 [118], EPHX2 [119] and FAM3C […”
Section: Discussionmentioning
confidence: 99%